Changes in the distribution of income and the new economic model in Jamaica - King, Damien (ECLAC SantiagoCL, 2000)
Examines the distributional changes in Jamaica in order to explain the paradox of a dramatic decline in inequality during and after a period of economic reform, and, after 1992, in the presence of macroeconomic stagnation.